Identify and deliberate on the prevailing game technologies towards IMO decarbonisation goals - Sim, Wei Han (Nanyang Technological University, 2022)
This paper provides a quantitative analysis of the current feasibility of ships adopting alternative fuels, as well as highlight the various opportunities and challenges each selected alternative fuel faces in adoption. To achieve our objective, we conducted an in-depth analysis of the current state of technologies based on data available online and through industry conferences, as well as performed targeted interviews on key decision makers in various maritime sectors including regulatory bodies, maritime education providers as well as ship management firms. We also conducted a survey among members of the industry to better understand their views on alternative fuels. We then integrated all the data into a tabular form for easy comparison. We derived that biofuel is the best performing alternative fuel based on our comparison parameters, and through our surveys and interviews, we realised that the maritime industry is very aware of the need to decarbonise, but they have divided opinions on what the prominent alternative fuel will be in the future. They have also stated fuel safety as the most critical factor in fuel selection. This study provides a basis for selecting an alternative fuel suitable for an organisation, and with further maturity of alternative fuel technologies in time, will provide clarity on which alternative fuel will best suit the needs of the industry.